Japanese MNCs Investment Objectives and Subsidiary Performance - Mohamad, Norhidayah; Hoshino, Yasuo (2012)
This study explores the Japanese MNCs investment objectives and their subsidiary’s performance in host-county. We found five main investment objectives by Japanese MNCs generally for establishing overseas or product network followed by obtain the local market, establish overseas distribution, information gathering and cheap labor cost. China in East Asia region indicates the highest number of Japanese MNCs outward FDI followed by Southeast Asia region (Singapore, Thailand, and Malaysia) in year 2003 and 2009. The high number of Japanese MNCs in Asia may be influence by bilateral and regional approaches to take advantage of Free Trade Agreement (FTA). Our empirical results also shows that Japanese investment in Asia region more prefer to choose ‘obtain local market’ in the early stage of entering to host country and revise to new investment objective after certain period of time to remain the firm’s profitability.